Dampak Inisiatif Ramah Lingkungan dan Efisiensi Biaya terhadap Profitabilitas Bank: Risiko Kredit Merupakan Penghalang atau Pendorong? - Ridwansyah Ridwansyah; Wiraputra, Jhody; Palupi Pratiwi; Okta Sari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze and prove empirically the influence of green banking and operational efficiency on the profitability of banks listed on the Indonesia Stock Exchange (IDX), as well as examine the role of credit risk as a moderating variable in the relationship. The research method used is a quantitative approach with secondary data sourced from the annual reports of banking companies during the observation period. Data analysis techniques were performed using multiple linear regression analysis and Moderated Regression Analysis (MRA) to test the effects of interaction between variables. The results showed that operational efficiency has a significant negative effect on profitability, while credit risk has a significant positive effect. On the other hand, green banking was found to have no effect on profitability. Furthermore, credit risk proved to be able to moderate the effect of operational efficiency on profitability, but not able to moderate the effect of green banking on bank profitability.